Robert Motherwell and the New York School storming the citadel (Home Vision, distributor, 1990)
This program from the PBS American masters series explores the Abstract Expressionist movement and presents a portrait of its most important artist : Robert Motherwell (1915-1991). Featured are Motherwell's last major interview, archival footage and photographs of other Maverick artists (Jackson Pollock, Willem de Kooning, Mark Rothko, Franz Kline), of Greenwich Village where they lived, and of events that shaped their lives. Also includes interviews with art critics and historians.